Optimalisasi Kemampuan Bertanya Siswa: Pemberdayaan Guru SMA di Desa Cinta Asih, Karawang - Suryaratri, Ratna Dyah; Ariyani, Mira (Jendela Akademika, 2023)
The paradigm shift in the Indonesian education systemwhere teacher-centered learning is transitioning towards student-centered learning isemphasizedin schools. However, many teachers still adhere to the old paradigm in their teaching practices. The main challenges faced are the lack of awareness and difficulties in implementing the new paradigm. Theobjective of thiscommunity empowermentis to change these perceptions through direct classroom training. The focus of theactivityatSMA 1 Pangkalan -Karawang is to enhance teachers’awarenessof students' ability to ask questions and seek academic support in the classroom. The participation of 27 teachers from different levels and subjects in this services resultedfindings that significantteaching strategies tailored to students' needs can encouragestudent questioning in the classroom. Furthermore, teacherswere able to identify students’needs and provide knowledge and questioning skills that encouragethe development of independent learners. The outcomes of this activityinclude increased teacher awareness of the importance of student questioning behavior,leading to a shift in mindset and departure from the old paradigm. Additionally, it is hoped that this initiative can be sustained in empowering teachers in other areas.